Attitudes Shape and Sustain Achievement - Subramanian, K. R. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
Business environment is dynamic and organizations cope with these changes in different ways depending on their products and market requirements. More and more organizations today are driven by the profit orientation, rightly so, and organizational achievement is measured in terms of returns to shareholders and stake holder interests. Whereas the stated objectives of non-profits are laudable what baffles one is the attitude and orientation of these organizations and people working for them. One can easily understand that the orientations of organizations differ with respect to their objectives. But there is one constant factor in all these. That is, the attitude, that drives achievement orientation. But it is difficult to sustain attitudes because of the environmental changes in culture and social acceptance factors. This paper explores the role of attitudes in sustaining achievement orientation that will propel organizations to growth. An incisive analysis of successful organizations reveal their constant attitude towards a welfare organization has propelled them to a position of prominence. This research paper will explore the kinds of Employer/Employee attitudes that will propel future organizations to growth and sustenance.